2001
DOI: 10.1046/j.1365-2591.2001.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Dye penetration in dry and water‐filled gaps along root fillings

Abstract: Methylene blue penetrates along root fillings more easily in dry gaps than in water-filled gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A large number of studies have used methylene blue as a dye (28,34,45) because it is inexpensive, easy to handle, has a high degree of staining (46) and has a molecular weight lower than that of bacterial toxins (47). Some researchers have suggested that methylene blue exhibits leakage similar to butyric acid (48), a microbial metabolic product with greater penetration than Indian ink.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have used methylene blue as a dye (28,34,45) because it is inexpensive, easy to handle, has a high degree of staining (46) and has a molecular weight lower than that of bacterial toxins (47). Some researchers have suggested that methylene blue exhibits leakage similar to butyric acid (48), a microbial metabolic product with greater penetration than Indian ink.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is difficult to eliminate the trapped air by applying low pressure to small empty spaces, including those measuring 2 μm in diameter, which are permeable to bacteria (53). Kontakiotis et al (45) investigated the influence of hydration on voids within the root canal obturation materials using a fluid transport model and dye penetration, in which air was applied to eliminate water from the voids in one group and showed that methylene blue penetrated more easily into dry gaps than into water-filled gaps. Methylene blue penetrated along air-filled gaps by capillary action, whereas it penetrated into water-filled gaps by diffusion (21).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies used methylene blue as dye (17,19,29) because it is inexpensive, easy to manipulate, has a high degree of staining and a molecular weight even lower than that of bacterial toxins (17). It has been suggested that methylene blue presents the same leakage as butyric acid (30), a microbial metabolic product that has greater penetration than Indian ink.…”
Section: Methodology That Uses Dyesmentioning
confidence: 99%
“…In this study, methylene blue dye penetration was used. Dye penetration experiment using various types of dyes (eosin, methylene blue, black India ink, Procion brilliant blue, and others) is widely used 32,33) because it is inexpensive, easy to manipulate, and it has a high degree of staining property. Also it has molecular weight even lower than that of bacterial toxins, so it has similar leakage to butyric acid, which is a microbial metabolic product 34) .…”
Section: Discussionmentioning
confidence: 99%